Predictors of changing patterns of adherence to containment measures during the early stage of COVID-19 pandemic: an international longitudinal study - Chong, Yuen Yu; Chien, Wai Tong; Cheng, Ho Yu; Lamnisos, Demetris; Lubenko, Jelena; Presti, Giovambattista; Squatrito, Valeria; Constantinou, Marios; Nicolaou, Christiana; Papacostas, Savvas S.; Aydin, Gökçen; Ruiz, Francisco J.; et al. (My University, 2023)
Identifying common factors that affect public adherence to COVID-19 containment measures can directly inform the development of official public health communication strategies. The present international longitudinal study aimed to examine whether prosociality, together with other theoretically derived motivating factors (self-efficacy, perceived susceptibility and severity of COVID-19, perceived social support) predict the change in adherence to COVID-19 containment strategies.
Keywords: Adherence; Coronavirus; Disease containment measures; Longitudinal study; Prosociality